28.8k views
2 votes
A. Simplify the Rational Exponent:1. (-125 a^3)^(2/3)

User Manthan
by
5.0k points

1 Answer

3 votes

Solution

We want to simplify


(-125a^3)^{(2)/(3)}

Note: Useful Tools


\begin{gathered} (1).\text{ }(a^mb^n)^{(1)/(r)}=a^{m*(1)/(r)}* b^{n*(1)/(r)} \\ \\ (2).\text{ }-125=-5*-5*-5=(-5)^3 \end{gathered}

So to solve the question


\begin{gathered} (-125a^3)^{(2)/(3)}=(-125* a^3)^{(2)/(3)} \\ \\ (-125a^3)^{(2)/(3)}=((-5)^3* a^3)^{(2)/(3)} \\ \\ (-125a^3)^{(2)/(3)}=(-5)^{3*(2)/(3)}* a^{3*(2)/(3)} \\ \\ (-125a^3)^{(2)/(3)}=(-5)^2* a^2 \\ \\ (-125a^3)^{(2)/(3)}=25* a^2 \\ \\ (-125a^3)^{(2)/(3)}=25a^2 \end{gathered}

User Arry
by
5.1k points